A study on resident perception towards rainwater harvesting application in domestic building / Muhammad Khusairy Rohimi - Rohimi, Muhammad Khusairy (Faculty Architecture, Planninng and Surveying, 2014)
With the increasing of the pure water demand due to the increasing of population this country makes the water sources have been decreasing day by day. For overcoming the water shortage problem, all people must take responsibility to save the water sources. Malaysia has a large amount of rainfall annually, and this gives a advantages for this country to overcome the water shortage problems, but lots of people still not aware about the water sources from rainfall for their own uses. The problem of water in Malaysia is several of the main topics in this country. To make sure a sustainable development, the innovative way has been introduced to the country which is the rainwater harvesting system. The aim of this research is to promote rainwater harvesting system application among residents of the domestic buildings including to achieve three objective of this study which is to identify the resident opinion towards the benefit, to investigate problems that are related and to give recommendation to make an improvement of the rainwater harvesting system for the domestic building. The primary data collection method is questionnaire survey and unstructured interviews, secondary sources which is literature review. The study were conducted at three case studies which is case study 1 at Jalan 9/5, Seksyen 9, kota damansara, the case study 2 at Legian Residence in Ken Rimba and the case study 3 at Taman Daya Maju in Meru, Klang. The result of this research show that the knowledge on rainwater harvesting among the resident is neutral, which need to be improved for their own benefit by using rainwater harvesting system. The rainwater harvesting system design need to be more friendly towards user, in term of application and maintenance. From this study, the recommendation for the future study that can cover on the roles of parties involved to promote the rainwater harvesting towards application to all new housing project.